2017
DOI: 10.1128/aac.01305-16
|View full text |Cite|
|
Sign up to set email alerts
|

Favipiravir Pharmacokinetics in Nonhuman Primates and Insights for Future Efficacy Studies of Hemorrhagic Fever Viruses

Abstract: Favipiravir is an RNA polymerase inhibitor that showed strong antiviral efficacy in vitro and in small-animal models of several viruses responsible for hemorrhagic fever (HF), including Ebola virus. The aim of this work was to characterize the complex pharmacokinetics of favipiravir in nonhuman primates (NHPs) in order to guide future efficacy studies of favipiravir in large-animal models. Four different studies were conducted in 30 uninfected cynomolgus macaques of Chinese (n ϭ 17) or Mauritian (n ϭ 13) origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…In that report, the systemic clearance of FAV was found to be significantly decreased over time. Similar PK properties were also observed in preclinical studies, and these properties were explained by enzyme-mediated elimination with concentration-dependent inhibition (26). Thus, we adapted a previously developed PK model for the autoinhibition of FAV clearance during repeated administration (27).…”
Section: Pires De Mello Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 52%
“…In that report, the systemic clearance of FAV was found to be significantly decreased over time. Similar PK properties were also observed in preclinical studies, and these properties were explained by enzyme-mediated elimination with concentration-dependent inhibition (26). Thus, we adapted a previously developed PK model for the autoinhibition of FAV clearance during repeated administration (27).…”
Section: Pires De Mello Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 52%
“…16 Pharmacokinetic analysis of intravenous favipiravir in cynomolgus macaques after repeated doses indicates obvious nonlinear pharmacokinetics over time and over a range of doses, and a continuous decline in plasma concentration after 7 days of continuous administration in the nonhuman primates is also observed. 17 Data obtained from 66 patients for experimental treatment with favipiravir for EVD (named as the JIKI trial) indicated that the steady-state trough concentration notably decreased on day 4 (25.9 µg/mL) as compared with day 2 (46.1 µg/mL), which supports a decrease in drug concentration after continuous use. 18 To further understand the in vivo biodistribution and kinetics of uptake and clearance of favipiravir after a single and repeated administration, an 18 F radiolabeled favipiravir ([ 18 F]favipiravir) was developed.…”
Section: Pharmacokinetics Of Favipiravirmentioning
confidence: 93%
“…(horizon 2020 grant 666092) , was set up to evaluate favipiravir efficacy in a context of emergency. The first aim of mathematical modeling was to find the optimal dosing regimen of favipiravir in patients with EVD, for which the drug’s half‐maximal effective concentration (EC 50 ) was much larger than against most strains of influenza virus 8 . The dosing regimen of favipiravir approved in Japanese patients for influenza was 1,600 mg twice daily the first day followed by 600 mg twice daily from the second to the fifth day.…”
Section: Favipiravir In Humans Infected With Evdmentioning
confidence: 99%
“…In the last years, our group was involved in the evaluation of favipiravir, an anti‐influenza drug approved in Japan, that has shown activity against a variety of other RNA viruses, in particular Ebola, Lassa fever, Marburg, Nipah, and Zika viruses 7‐9 . The main advantages of applying an approved agent to treat a new indication, a process called “drug repurposing,” are that the drug is available in large quantities and that safety studies have already been conducted on large populations 10 .…”
mentioning
confidence: 99%